The Relationship Between Individual Characteristics and Work Factors With The Level of Lower Back Pain Complaints Among Workers in The Macaroni Industry in Malang Regency - Misbahul Subhi; Ratu Kumaerah; Beni Hari Susanto (Green Publisher Indonesia, 2025)
This study examines the correlation between individual characteristics, work factors, and the severity of lower back pain complaints among workers in the macaroni industry in Malang Regency. The study's background encompasses the notion that individual characteristics and work factors may serve as risk factors for lower back pain complaints. Everyone in the workplace must apply occupational health and safety to achieve the highest level of physical, mental, and social health through preventive and curative measures against work-related health disorders. This study uses a quantitative approach with the cross-sectional method and the chi-square test to determine the relationship between independent variables and dependent variables. The results of the analysis show that individual characteristics such as age, BMI, and education have a significant relationship with lower back pain complaints, while gender is not significant. Work factors such as length of service also show a significant relationship with lower back pain complaints, while length of service does not show a significant relationship